2018
DOI: 10.1016/j.fm.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen availability and strain combination modulate yeast growth dynamics in mixed culture fermentations of grape must with Starmerella bacillaris and Saccharomyces cerevisiae

Abstract: Starmerella bacillaris (synonym Candida zemplinina) is a non-Saccharomyces yeast that has been proposed as a co-inoculant of selected Saccharomyces cerevisiae strains in mixed culture fermentations to enhance the analytical composition of the wines. In order to acquire further knowledge on the metabolic interactions between these two species, in this study we investigated the impact of oxygen addition and combination of Starm. bacillaris with S. cerevisiae strains on the microbial growth and metabolite product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…This decline in the population of Starm. bacillaris can be due to several parameters such as lower fermentative capability of this species compared to S. cerevisiae due to several parameters such as cell to cell contact (Englezos et al, 2019 ), limited oxygen (Englezos et al, 2018b ) and nutrient availability as suggested by Englezos et al ( 2016b ). In the case of Wa -dose fermentation, the sugar consumption rate displayed a faster utilization of glucose than fructose, however, this does not seem to affect the implantation of S. cerevisiae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decline in the population of Starm. bacillaris can be due to several parameters such as lower fermentative capability of this species compared to S. cerevisiae due to several parameters such as cell to cell contact (Englezos et al, 2019 ), limited oxygen (Englezos et al, 2018b ) and nutrient availability as suggested by Englezos et al ( 2016b ). In the case of Wa -dose fermentation, the sugar consumption rate displayed a faster utilization of glucose than fructose, however, this does not seem to affect the implantation of S. cerevisiae .…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of Starm. bacillaris throughout fermentation can be attributed to its strong fructophilic characteristics, limited nitrogen requirements and the ability of this species to excrete some branched amino acids (Englezos et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the inhibition of oxygen concentration on microorganism respiration, the DO concentration in the system should be above the critical dissolve oxygen (C cr ) concentration. The C cr for yeast is normally 1.8% (Englezos et al 2018). It suggested that no inhibition on the respiration should have occurred even at DO level of 10%-20%.…”
Section: Dissolved Oxygen Concentration Effect On Cell Growthmentioning
confidence: 99%
“…The presence of a large quantity of WG bunches in fermentation vats reduces the ratio of alcoholic fermentation in the liquid portion present at the bottom of tanks. In particular, the low oxygen availability in the early steps of winemaking is a non‐optimal condition for yeast development, because oxygen is essential to ensure cell replication and synthesis of cell membrane constituents involved in resistance to ethanol (Salmon ; Englezos et al ). On the other hand, anaerobic facultative micro‐organisms such as lactic acid bacteria (LAB) could find optimal development conditions (Liu ), and it is often possible to observe bacterial malic acid consumption during the first days of carbonic fermentation.…”
Section: Introductionmentioning
confidence: 99%